Preparation and Characterization of Protein-Based Hydrogel: Cottonseed Protein Grafted with 2-Acrylamido-2-Methylpropanesulfonic Acid (AMPS) - Dehenenet Flatie Tassw; Tamrat Tesfaye; Murugesh Babu K. (Advances in Materials Science and Engineering)
Using synthetic polymers in the production of superabsorbent polymers offers significant advantages such as low cost, extended service life, and a high water absorption rate. However, concerns about the environmental impact and potential adverse effects on plant growth arise from the degradation products of these polymers after disposal. In addition, handling these polymers can cause rashes, irritations, and even toxic shock syndrome. To overcome these issues, researchers are exploring the synthesis of superabsorbent polymers from natural sources. Cottonseed protein is identified as a potential natural polymer for the synthesis of natural superabsorbent polymers. Notably, there is no existing research on hydrogel synthesis using cottonseed protein and 2-acrylamido-2-methylpropanesulfonic acid (AMPS). This study addresses this gap by focusing on modifying cottonseed protein (CSP) through graft copolymerization, utilizing the partially neutralized form of 2-acrylamido-2-methylpropanesulfonic acid (AMPS) in a water-based solution. N,N-methylene bisacrylamide serves as the crosslinking agent, while potassium persulfate (PPS) and sodium bisulfite (SBS) function as redox initiators. The optimization of hydrogel synthesis conditions was achieved using Design Expert-11 software, adjusting the AMPS to CSP ratio. The research reveals that the hydrogel reaches its maximum swelling capacity (195.7 g/g) with 0.03 g of MBA, 0.01 g of PPS, 0.01 g of SBS, and a 1wt% AMPS to CSP ratio. Swelling properties were assessed under diverse pH conditions, and the study delved into swelling kinetics (both pseudo-first-order model and pseudo-second-order model) and performance under different loads. Grafting evidence was validated through FTIR analysis. The maximum water uptake was obtained when there was no load, and the pH value was around neutral (7). In conclusion, the results indicate that the developed hydrogel holds a promise for applications in water retention, reducing water loss, and serving as an environment-friendly, biocompatible superabsorbent polymer so we can use such hydrogel in biomedical applications.